1992
DOI: 10.3109/08923979209009231
|View full text |Cite
|
Sign up to set email alerts
|

Pidotimod Stimulates Natural Killer Cell Activity and Inhibits Thymocyte Cell Death

Abstract: Experiments were performed to analyze the possible effect of the immunomodulating agent Pidotimod (3-L-pyroglutamyl-L-thiazolidine-4-carboxylic acid) on mouse Natural Killer (NK) cell activity and glucocorticoid hormone(GCH)-induced thymocyte apoptosis. The results indicate that in vivo treatment with Pidotimod (200 mg/Kg ip for 5 days) causes a significant increase in NK activity and in vitro treatment produces a significant reduction of dexamethasone-induced thymocyte apoptosis. This inhibition appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The studies indicate that pidotimod has an immunomodulatory activity on both innate and adaptive immune response. It could promote natural killer cell functions,enhance phagocytic activity of monocytes, or change the chemotaxis of neutrophil . On the other hand, pidotimod could promote lymphocyte proliferation to restore the CD4+/CD8 ratio or increase interleukin‐2 (IL‐2) and interferon release.…”
mentioning
confidence: 99%
“…The studies indicate that pidotimod has an immunomodulatory activity on both innate and adaptive immune response. It could promote natural killer cell functions,enhance phagocytic activity of monocytes, or change the chemotaxis of neutrophil . On the other hand, pidotimod could promote lymphocyte proliferation to restore the CD4+/CD8 ratio or increase interleukin‐2 (IL‐2) and interferon release.…”
mentioning
confidence: 99%
“…At last, this work also provides a meaningful mode of action for PTD and highlights its clinical significance as an immunotherapeutic medicine for cancer in restoring damaged immune system of cancer patients after chemotherapy. 30,31 Furthermore, we could use PTD of matured DC are with more protrusions as well as rougher surface ( Fig. 3), which usually indicates increased expression of key surface markers or receptors; (3) reduction of phagosomes inside the DC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…132 Early studies in humans demonstrated that pidotimod induces the bactericidal activity of alveolar macrophages, 133 while also activating innate immunity at NK cell level activity. 134 Recently, research has shown that monocyte adhesion and chemotaxis, as well as the migration of IL-2 activated T cells, induced by pidotimod requires the activation of the phosphatidylinositol 3-kinase pathway (PI3K/Akt) signaling pathway through the CXC chemokine receptor 3A (CXCR3A) isoform. 135 Pidotimod is also capable of inducing the maturation of DCs and increasing the expression of major histocompatibility complex class II cell surface receptor (HLADR) and co-stimulatory molecules CD83 and CD86.…”
Section: Synthetic Molecules (Pidotimod)mentioning
confidence: 99%